Partição da deformação no limite entre o terreno granito-greenstone de Rio Maria e o Cinturão Itacaiúnas, Carajás (PA) - VIEGAS, Luís Gustavo Ferreira (Universidade Federal do Pará, 2019)
This research is primarily concerned with the tectonic evolution of an Archaean crustal segment of the Amazonian Craton which is thought to encompass two distinct Archaean terranes: the Rio Maria Granite-Greenstone Terrain, to the south, and the Itacaiúnas Belt, to the north. These two terranes show similar lithologies and a short range variation in geochronological ages, but their structural pattern differs significantly. The rocks exposed in the domains of the Rio Maria Granite-Greenstone Terrain comprise mainly TTG series (2.9 – 2.86 Ga), alkaline plutons (2.86 Ga) and greenstone belts (2.9 Ga), which display ages older than those found on the Itacaiúnas Belt. A compositional layering can be seen in the tonalites, trondhjemites and granodiorites, and a magmatic foliation is locally observed in the monzogranites and syenogranites. These fabrics strike NW-SE to E-W with medium to shallow dips to NE and SW. The linear fabrics associated with these structures are only locally developed, and generally show shallow plunges to SE. In the Itacaiúnas Belt the main structural feature is a coarse mylonitic foliation present in the tonalites, granodiorites and migmatites associated with the Xingu Complex (2.7 Ga), and also in the syenogranites and alkali-feldspar granites of the Plaquê Suite (2.7 Ga). This foliation is steeply dipping to N and S, trending E-W to NW-SE. The stretching lineation present in the mylonitc foliation planes shows shallow dips to NE, SE, NW and SW. Five structural domains were defined based on strain facies analysis method. From north to south, these facies show partition of displacement into compressional and strike-slip components and also distinct fabric generation patterns. Facies V and IV, located in the southern portion of the studied area, are characterized by a dominant compressional component of frontal to oblique nature associated with structures generated by magmatic to submagmatic flow. The central portion of the study area is marked by facies III, which represents a junction between different structural patterns and fabric generation processes. This facies shows interplay between compressional and strike-slip displacements, as well as fabrics developed either by magmatic flow and solid-state flow. The northern portion of the studied area comprises facies II and I, which contain fabrics derived mainly from plastic strain associated with a high degree of planar transposition. The overall kinematic pattern is mainly sinistral, with dextral displacements observed where the compressional component of partitioned transpression is stronger. The two northern facies display sinistral displacement, while facies III and facies IV show a combination of compressional and transcurrent motion. Local shear sense indicators suggest sinistral displacement for facies V. The geological evolution of the studied area involved two main stages: i) a first stage of emplacement of TTG granitoids in an Archaean protocrust mainly located at the region of Rio Maria Granite Greenstone Terrain, and ii) a second stage marked by shear zone nucleation, magma generation and pluton emplacement in a partitioned transpressional setting. The partitioned transpression was responsible for nucleation of a regional scale set of shear zones which partitioned the deformation across the area. In the northern facies, the deformation pattern is mainly characterized by strike-slip transposition of planar fabrics formed under solid state conditions. To the south, magmatic flow is dominant and compressional components of transpression are evident. The regional shear zones also worked as conduits for magma ascension and emplacement at higher levels of the crust. These magmas were derived from partial melting of the TTG series and are mainly alkaline and/or migmatitic in composition. The structural pattern observed in the area between the Rio Maria Granite-Greenstone Terrain and the Itacaiúnas Belt is interpreted as a result of progressive deformation in a sinistral partitioned transpressional setting. This strain pattern comprised geometric and kinematic partitioning in zones of strike-slip displacement and compressional components, and also distinct fabric generation patterns ranging from magmatic to solidstate flow. These characteristics suggest that these two terranes are involved in the same transpressional event and, as such, the Itacaiúnas Belt can be interpreted as a crustal fragment associated with the Rio Maria Granite-Greenstone Terrain, which evolution is marked by progressive events of tectonic reworking and granite emplacement.